Implementation of Animation Video Media with the help of the animeker application to Improve Student Learning Outcomes - Dewi, Imega Syahlita; Dewi, Delvi Avriana (Science Education and Application Journal, 2023)
This study aims to improve student learning outcomes through the application of animation media with the help of animeker applications in Science Subject class X-TPM 1 SMK Negeri 1 Nganjuk. This research is a classroom action research consisting of the stages of planning, action, observation and reflection. Data collection was carried out using test techniques. Test techniques were carried out by giving assignments at the end of the learner. Data were analyzed descriptively and quantitatively to compare the completeness of each cycle. The results showed that student learning outcomes increased from cycle I to cycle II after using animated video media. Based on the test results in the first cycle, the classical average is 82.72%. Whereas classically, that is 90% of students who must reach a grade level of 70 or more. As for the achievement of the average value in cycle II of 94.12% of students have scores above the KKM. The results showed that student learning outcomes increased from Cycle I to Cycle II after using animated video media assisted by the animeker application.